Dietary and Gut Microbiota Polyamines in Obesity- and Age-Related Diseases - Ramos-Molina, Bruno; Queipo-Ortuño, Maria Isabel; Lambertos, Ana; Tinahones, Francisco J.; Peñafiel, Rafael (Frontiers in Nutrition, 2019)
The polyamines putrescine, spermidine, and spermine are widely distributed polycationic compounds essential for cellular functions. Intracellular polyamine pools are tightly regulated by a complex regulatory mechanism involving de novo biosynthesis, catabolism, and transport across the plasma membrane. In mammals, both the production of polyamines and their uptake from the extracellular space are controlled by a set of proteins named antizymes and antizyme inhibitors. Dysregulation of polyamine levels has been implicated in a variety of human pathologies, especially cancer. Additionally, decreases in the intracellular and circulating polyamine levels during aging have been reported. The differences in the polyamine content existing among tissues are mainly due to the endogenous polyamine metabolism. In addition, a part of the tissue polyamines has its origin in the diet or their production by the intestinal microbiome. Emerging evidence has suggested that exogenous polyamines (either orally administrated or synthetized by the gut microbiota) are able to induce longevity in mice, and that spermidine supplementation exerts cardioprotective effects in animal models. Furthermore, the administration of either spermidine or spermine has been shown to be effective for improving glucose homeostasis and insulin sensitivity and reducing adiposity and hepatic fat accumulation in diet-induced obesity mouse models. The exogenous addition of agmatine, a cationic molecule produced through arginine decarboxylation by bacteria and plants, also exerts significant effects on glucose metabolism in obese models, as well as cardioprotective effects. In this review, we will discuss some aspects of polyamine metabolism and transport, how diet can affect circulating and local polyamine levels, and how the modulation of either polyamine intake or polyamine production by gut microbiota can be used for potential therapeutic purposes.